The death of Jesus - Coetzee, J. M., 1940- (Harvill Secker, 2019)
"After The Childhood of Jesus and The Schooldays of Jesus, the Nobel prize-winning author completes his haunting trilogy with a new masterwork, The Death of Jesus. In Estrella, David has grown to be a tall ten-year-old who is a natural at soccer, and loves kicking a ball around with his friends. His father Simón and Bolívar the dog usually watch while his mother Inés now works in a fashion boutique. David still asks many questions, challenging his parents, and any authority figure in his life. In dancing class at the Academy of Music he dances as he chooses. He refuses to do sums and will not read any books except Don Quixote. One day Julio Fabricante, the director of a nearby orphanage, invites David and his friends to form a proper soccer team. David decides he will leave Simón and Inés to live with Julio, but before long he succumbs to a mysterious illness. In The Death of Jesus, J. M. Coetzee continues to explore the meaning of a world empty of memory but brimming with questions"--